Islamic Banking and Financial Development: A Cross-Country Analysis - Baita, Abubakar Jamilu; Umar, Umar Habibu; Shawa, Jamilu Sani (International Journal of Islamic Economics and Finance (IJIEF), 2024)
Islamic banking has become an integral part of the modern financial system. Therefore, this study examined the effect of Islamic banking on financial development in countries with a matured practice of Islamic finance. These countries include Iran, Saudi Arabia, Malaysia, UAE, Kuwait, Qatar, Turkey, Bangladesh and Indonesia. Besides, we collected data on Islamic banks' assets and financial development indicators over nine (9) years between 2012 and 2020. The study applied heteroscedastic panel corrected standard errors (HPCSE) regression model to estimate results. The findings indicated that Islamic banks contribute significantly to improving financial development after controlling for banking characteristics (credit risk and capital adequacy ratio) and macroeconomic factors (real per capita GDP, inflation and trade openness). Due to data limitations, this study covers only nine countries over nine years (2012 -2020). The findings provided insight into the contribution of Islamic banks to financial development, which can motivate regulatory authorities and policymakers to improve the practice of Islamic banking and finance through the provisions of enabling and motivational regulations and policies. This study provided a novel contribution as this issue is underresearched. Most existing studies concentrate on the macroeconomic and institutional determinants of financial development, thus relegating the role of Islamic banking in spurring financial development.